Distance Education in Africa: A Longitudinal Study of the Perceptions of 2,416 Students - Karsenti, Thierry; Collin, Simon (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2013)
Distance Education (DE) holds particular promise for Africa, where higher education systems must cope with multiple constraints. However, there are many obstacles to the development of DE, including inadequate computer equipment and lack of professional skills. Against this background, this article presents the results of a longitudinal study on DE programs offered to students in Africa. Using quantitative analyses of questionnaires and qualitative analyses of interviews, the contributions of DE to the professional development of Africans are examined in the aim of gaining a deeper understanding of the dynamics at play when students enroll in a DE program.